PENGARUH PENGARUH JOB INSECURITY DAN INTENTION TO LEAVE TERHADAP KINERJA KARYAWAN KONTRAK DI DINAS TENAGA KERJA KOTA SURABAYA - Dina Novita; Pinky Pininta Dewi (Gapenas Publisher, 2021)
This study aims to determine the effect of Job Insecurity and Intention to Leave on the Performance of Contract Employees at the Surabaya City Manpower Office. The approach used is quantitative with the type of inferential research. The sample in this study was 30 employees in the Surabaya City Manpower Office. The analysis technique used is Partial Least Square (PLS). This study proves that Job Insecurity has a positive effect on employee performance at the Surabaya City Manpower Office. In this study, job insecurity is influenced by factors such as role conflict, role ambiguity, and organizational change. Intention To Leave has a positive effect on employee performance at the Surabaya City Manpower Service